Potentiation of erythropoiesis in vitro by dexamethasone. - Golde, D W; Bersch, N; Cline, M J (The Journal of Clinical Investigation, 1976)
The effect of dexamethasone on erythropoiesis was examined in vitro. Hematopoietic cells from 13-day mouse fetal livers were cultured for 48 h in the presence or absence of erythropoietin and erythroid colonies enumerated. Colony formation occurring in cultures containing no added erythropoietin was inhibited by the incorporation of antierythropoietin antibody, suggesting that these colonies formed in response to endogenous hepatic erythropoietin. Maximal colony formation was observed with 0.5 U/ml of sheep erythropoietin. Dexamethasone increased erythroid colony formation with peak stimulation at 10(-9) M. Dexamethasone potentiation was most marked in cultures containing less than maximally stimulating concentrations of erythropoietin. The cells required only a brief exposure to glucocorticosteroid to exhibit the augmented cloning capacity, and dexamethasone stimulation was inhibited by progesterone (10(-6) M). A comparable response to dexamethasone was observed in cultures of adult murine and human bone marrow erythroid progenitors, implying that the phenomenon is not peculiar to fetal cells and is not dependent on the presence of fetal hepatocytes. These data suggest that erythroid progenitor cells possess a glucocorticoid receptor mechanism that can modulate the response to erythropoietin in vitro. Images